ANGPTL4 and IGF-1 expressions in relation to molecular subtypes in young invasive breast carcinoma - Kamaludin, Zaleha (2020)
Invasive Breast Carcinoma (IBC) in a young patient has been reported to be more aggressive. Angiopoietin-like protein 4 (ANGPTL4) is part of angiopoietin family proteins and plays a critical role in cancer growth and contributes to metastasis. Meanwhile, insulin growth factor-1 (IGF-1) is a potent mitogen that can stimulate breast cancer development with metastatic potential. This study aimed to investigate the possible association of young IBC with the expression of IGF-1 and ANGPTL4. A cross-sectional study was conducted using 75 archived formalin-fixed paraffin-embedded tissue blocks of young IBC with age <45 years old. The molecular IBC subtype was classified into luminal A, luminal B, HER2 overexpression, and triple negative based on the surrogate markers of ER, PR and HER2. All samples were stained for ANGPTL4 and IGF-1 by immunohistochemistry method. The age of patients ranged from 23-44 years old, with the mean age of 37 (SD 5.48). Luminal A 28(37.7%), were the highest molecular subtype in young IBC followed by triple negative 20(26.7%), luminal B 15 (20%) and HER2 overexpression 12 (16%). Among 75 cases of young IBC patient, 51(68%) of them were immunopositive for ANGPTL4, meanwhile, 67(89%) were positive towards IGF-1. Both proteins were highly expressed in high-grade IBC, larger tumour size, and lymph node metastasis. 19(37%) of luminal A subtype were positive for ANGPTL4 followed by triple negative 14(28%), luminal B 9(18%) and HER2 overexpression 8 (16%). The expression of IGF-1 was also high in luminal A 27(40.3%) but lowest in HER2 overexpression 10(14.9%). However, there was no significant association of ANGPTL4 (p=0.897) and IGF-1 (p=0.091) to molecular subtypes. Majority of young IBC shows ANGPTL4 and IGF-1 proteins expression towards luminal A. Moreover, these proteins were also highly expressed in high-grade IBC, larger tumour size, and lymph node metastasis. However, there were no significant association of molecular subtypes with both proteins. These findings may emphasise the use of these markers as a potential tool for understanding the tumour progression and metastatic behaviour. It is hoping these findings would assist in the development of new breast cancer management strategies that will improve the clinical outcomes. Thus, further study with a larger sample might be conducted to explore the role of ANGPTL4 and IGF-1 in invasive breast carcinomas.